-6•f (-3) - 5•g (-7) =
please help.
![6f 3 5g 7 please help class=](https://us-static.z-dn.net/files/d05/a8d05449c323c5917dee4d0918c562cc.png)
Answer:
-12
Step-by-step explanation:
The value of f(-3) is found by finding the point on the solid blue graph where x = -3. That point has a y-value of -3, so f(-3) = -3.
The value of g(-7) is found by finding the point on the dashed purple graph where x = -7. That point has a value of 6, so g(-7) = 6.
Putting these numbers into your expression gives ...
-6(-3) -5(6) = 18 -30 = -12